2021
DOI: 10.7860/jcdr/2021/48773.14845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Grading of Rotator Cuff and Labral Injuries in Shoulder Pain and Instability using MRI: ACross-sectional Study

Abstract: Introduction: Shoulder joint is a highly mobile joint but is prone for rotator cuff injuries and dislocations. It is necessary to accurately diagnose rotator cuff and labral injuries so that appropriate plan of action for treatment can be taken. Magnetic Resonance Imaging (MRI) can be used to diagnose and describe the extent of rotator cuff tendon and labral injuries and any secondary rotator cuff muscle abnormalities. Aim: To study the demographic profile of patients presenting with shoulder pain and instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…16,17 Chowdhary et al, also reported that shoulder pain more commonly occurred in older patients, but shoulder instability was more commonly seen in younger patients, with the most common age group affected being 21-30 years and all being males. 18 Virtual touch tissue imaging and quantification is software used in elastography for the qualitative and quantitative assessment of the stiffness of tissue. 16 In a study by Deng et al, on application of VTIQ SWE in diagnosing supraspinatus tendon tears, a red-yellow color graph was shown by the normal tendon, and the pathological tendon became soft, which was demonstrated by the VTIQ color map.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Chowdhary et al, also reported that shoulder pain more commonly occurred in older patients, but shoulder instability was more commonly seen in younger patients, with the most common age group affected being 21-30 years and all being males. 18 Virtual touch tissue imaging and quantification is software used in elastography for the qualitative and quantitative assessment of the stiffness of tissue. 16 In a study by Deng et al, on application of VTIQ SWE in diagnosing supraspinatus tendon tears, a red-yellow color graph was shown by the normal tendon, and the pathological tendon became soft, which was demonstrated by the VTIQ color map.…”
Section: Discussionmentioning
confidence: 99%